Implementation Risk in Accrual Accounting Reform: Internal Audit Readiness and the Risk of Institutional Decoupling in the Saudi Public Sector - Khaled Hamden Alshammari (Journal of Risk and Financial Management, 2026)
Accrual accounting reform can be formally adopted before the internal audit routines needed to assure it are operationally embedded. This exploratory diagnostic study examines perceived implementation risk among 95 internal audit professionals working in Saudi governmental entities. A content audit of an existing questionnaire showed that its original accrual-basis accounting application (ABAA), senior management support (SMS), and internal audit effectiveness (IAE) blocks combined conceptually adjacent benefit, support, resource, and outcome statements. The analysis therefore uses theory-guided, content-separated diagnostic domains and an item-level timeliness model rather than treating the original blocks as discriminant latent constructs or testing mediation. Within-respondent contrasts were assessed using paired t-tests and Wilcoxon signed-rank checks. Because timely completion is a five-category ordinal outcome, ordinal regression is the scale-respecting approach. The full five-predictor ordered-logit model was retained as a theory-complete diagnostic because E4 explicitly includes staffing, but its global proportional-odds restriction was rejected due to staffing. Accordingly, substantive ordinal inference and model-implied probabilities are based on the assumption-compatible reduced model excluding staffing, while the full model is reported transparently as a diagnostic sensitivity specification. Formal reform orientation exceeded applied reform capacity by 0.437 points (p < 0.001; dz = 0.441); visible governance and monitoring exceeded operational audit infrastructure by 0.674 points (p < 0.001; dz = 0.830); and perceived staffing sufficiency exceeded timely task completion by 0.800 points (p < 0.001; dz = 0.615). In the assumption-compatible reduced ordered-logit model, annual planning (b = 0.581, p = 0.016) and the accrual-aligned internal audit guide (b = 1.570, p < 0.001) were positively associated with timeliness; the corresponding full-model estimates were nearly identical. The OLS-HC3 robustness model accounted for 61.2% of respondent-level variation, although same-source response tendencies may contribute to this fit. The observed pattern is compatible with uneven layered institutionalization and a risk of decoupling between visible or formal elements and operational routines; it does not establish temporal sequencing, sector-wide prevalence, intentional symbolic compliance, or causal effects. Conclusions are bound by the cross-sectional, same-source design and the post hoc diagnostic use of an existing instrument that requires prospective validation.